INTERDEPENDENCE OF ECONOMIC AND ENVIRONMENTAL EFFICIENCY IN AGRICULTURE IN THE EUROPEAN UNION - Staniszewski, Jakub; Czyżewski, Andrzej (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of the study was to identify the most important determinants of economic and environmental efficiency of agricultural production in the EU countries in 2005, 2007, 2010 and 2013, with particular emphasis on structural conditions. The paper presents the results of modelling with the use of Eurostat data and methods of data envelopment analysis (DEA) and panel regression. In the case of economic efficiency, the importance of production concentration, understood as economic strength of farms, associated with an even distribution of production, was identified. In the case of eco-efficiency, its limiting factor turned out to be specialisation towards animal production. These results allow us to conclude that it is possible to achieve economic and environmental objectives at the same time, as none of the identified determinants was repeated in both models with the opposite sign. The results of the research are also a premise for the implementation of an active structural policy under the CAP after 2020.